Design and analysis of modular wheelchair for usage of handicap people - Mohd Amin, Mad Saad (2012)
The report begins with a preliminary research of human factor engineering and ergonomic study for the design of wheelchair. The main objective of this project is to select the best conceptual design using Pugh selection method also use of simulation in analyzing the critical part of the wheelchair modeling and evaluating the wheelchair design. The projects begin with make a questionnaire survey to the respondent’. From the survey, a total of 35 respondents’ has taken part. The survey consists of several parts such as personal information, general information of using wheelchair, and the ergonomic of wheelchair. The stress evaluation was carried out at lower back, buttock and knee; the gathered information through survey was applied in the redesign process. Three sketches have been sketched. Based on the sketches, Pugh selection concept has been used to select the best design. Next the sketches being draw into SolidWorks software and then go through to simulation process by using FEA, the design was analyzed using constant force. Improvement of critical parts such as seating support design was compared based on material used analysis on Stress Von Mises. At the end, when all the process mentioned above is done, the result for report writing is gathered.